2019
DOI: 10.1111/and.13242
|View full text |Cite
|
Sign up to set email alerts
|

Protective effects of silymarin on testis histopathology, oxidative stress indicators, antioxidant defence enzymes and serum testosterone in cadmium‐treated mice

Abstract: Cadmium is known as an oxidative stress‐inducing factor. Silymarin extracted from Silybum marianum is regarded as a potent antioxidant. The present study investigated the preventing effects of silymarin on cadmium chloride‐induced toxicity in terms of testis histopathology and serum testosterone level as well as oxidative stress indicators in mice. In addition, the activities of antioxidant defence enzymes was evaluated. Adult male mice were divided into four groups (n = 6 in each group): (a) control; (b) cadm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
17
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 21 publications
5
17
1
Order By: Relevance
“…Silymarin is also known as a potent antioxidant and several studies confirmed its protective effects in heavy metals‐treated spermatozoa (Abedi et al, 2016; Eskandari & Momeni, 2016a, 2016b; Hamid, Ahmed, & Tayawi, 2018). Recently, we showed that in cadmium‐treated mice, silymarin was able to compensate for the toxic effects of this environmental pollutant on testis histopathology and serum testosterone levels (Faraji et al, 2019) as well as serum antioxidant defence enzymes (Farjad & Momeni, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Silymarin is also known as a potent antioxidant and several studies confirmed its protective effects in heavy metals‐treated spermatozoa (Abedi et al, 2016; Eskandari & Momeni, 2016a, 2016b; Hamid, Ahmed, & Tayawi, 2018). Recently, we showed that in cadmium‐treated mice, silymarin was able to compensate for the toxic effects of this environmental pollutant on testis histopathology and serum testosterone levels (Faraji et al, 2019) as well as serum antioxidant defence enzymes (Farjad & Momeni, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…The slides were allowed to air‐dry and then photographed with a light microscope at 1000X magnification. Diameter of sperm nuclei was measured in at least 200 spermatozoa using the Motic software (Faraji et al, 2019).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Catalase (CAT) activity was measured according to the UV colorimetric method described by Aebi (1984) at 240 nm using the oxidising reaction of nitro blue tetrazolium (NBT) and H 2 O 2 as substrate (Faraji, Momeni, & Malmir, 2019;Vijaya Bharathi et al, 2015). The obtained supernatant was used for determination of antioxidant enzyme activity and levels of lipid peroxidation (MDA activity).…”
Section: Antioxidant Enzymes Activitiesmentioning
confidence: 99%
“…The obtained supernatant was used for determination of antioxidant enzyme activity and levels of lipid peroxidation (MDA activity). Catalase (CAT) activity was measured according to the UV colorimetric method described by Aebi (1984) at 240 nm using the oxidising reaction of nitro blue tetrazolium (NBT) and H 2 O 2 as substrate (Faraji, Momeni, & Malmir, 2019;Vijaya Bharathi et al, 2015). Superoxide dismutase (SOD) activity was determined according to the colorimetric method of Martin, Dailey, and Sugarman (1987) at 560 nm.…”
Section: Antioxidant Enzymes Activitiesmentioning
confidence: 99%